Tau Avoids the GTP Cap at Growing Microtubule Plus-Ends - Brian T. Castle; Kristen M. McKibben; Elizabeth Rhoades; David J. Odde (iScience, 2020)
Summary: Plus-end tracking proteins (+TIPs) associate with the growing end of microtubules and mediate important cellular functions. The majority of +TIPs are directed to the plus-end through a family of end-binding proteins (EBs), which preferentially bind the stabilizing cap of GTP-tubulin present during microtubule growth. One outstanding question is whether there may exist other microtubule-associated proteins (MAPs) that preferentially bind specific nucleotide states of tubulin. Here, we report that the neuronal MAP tau preferentially binds GDP-tubulin (KD = 0.26 μM) over GMPCPP-tubulin (KD = 1.1 μM) in vitro, as well as GTP-tubulin at the tips of growing microtubules, causing tau binding to lag behind the plus-end both in vitro and in live cells. Thus, tau is a microtubule tip avoiding protein, establishing the framework for a possible new class of tip avoiding MAPs. We speculate that disease-relevant tau mutations may exert their phenotype by their failure to properly recognize GDP-tubulin.